THE PARADIGM OF RELATIONSHIP BETWEEN TEACHER AND STUDENT IN THE PROCCESS OF TEACHING ORIENTAL LANGUAGE IN HIGHER SCHOOLS OF UZBEKISTAN. - Yunusova, Komiljonovna Nodira; Abduraxmatovna, Mubarakova Dilshoda (The journal of contemporary issues in business and government, 2021)
The process of teaching foreign languages consists of many components, with the inviolability of its fundamental foundations, approaches and principles, there are also variable components that require periodic updating. First of all, this is due to the changing living conditions under the influence of technical progress and, accordingly, with the specificity of perception and memorization of each new generation of students who come to universities. The change in the composition of skills and abilities acquired in secondary school, the ways of perceiving and processing information, the modification of the mechanisms of memorization and the formation of long-term memory cannot be overlooked by the teacher of a foreign language, who at a humanitarian university spends more time with students in the classroom than others, and due to smaller groups, it is in closer personal contact with trainees. Nowadays the process of teaching is filled with opportunities and challenges, but also with changes.The issueto be a teacher is changing, and being English as a Second Language (ESL) teacher involves and demands new teaching strategies,methods, new attitudes, activities, and perspectives for the classroom.